Manejemen Farmakologis Herpes Labialis : Tinjauan Pustaka - Isaura Dewi Fauzi; Rasmi Zakiah Oktarlina (Universitas Malahayati Lampung, 2025)
ABSTRACT Herpes labialis caused by herpes simplex virus type 1 (HSV-1) infection is a latent infectious disease with high prevalence globally, where socioeconomic changes and hygiene levels affect its transmission patterns. This study aims to evaluate the pharmacological management of herpes labialis through analysis of treatment methods and stages of HSV-1 infection to determine the optimal intervention strategy. The study was conducted using a literature study method on 281 articles from the PubMed, ScienceDirect, Garuda, and Google Scholar databases, which were systematically selected and analyzed. The results of the analysis showed that Acyclovir administration was most effective in the prodromal phase, with a combination of corticosteroids able to accelerate healing. Supplementation of vitamins B12 and D contributed to supporting the immune system, while the use of 0.2% chlorhexidine gluconate was effective in preventing secondary infections. Stress factors were identified as a predisposition to recurrence, so stress management education based on the 4M concept (Avoiding, Changing, Adapting, Accepting) is important. It was concluded that optimal management of herpes labialis requires an integrated pharmacological approach and psychosocial interventions. Further research is needed for the development of an HSV-1 vaccine and the improvement of community-based prevention education programs. Keywords: Herpes Labialis, Antiviral, HSV ABSTRAK Herpes labialis yang disebabkan oleh infeksi virus herpes simpleks tipe 1 (HSV-1), merupakan penyakit menular laten dengan prevalensi tinggi secara global, di mana perubahan sosial ekonomi dan tingkat kebersihan memengaruhi pola transmisinya. Penelitian ini bertujuan untuk mengevaluasi manajemen farmakologis herpes labialis melalui analisis metode pengobatan dan tahapan infeksi HSV-1 guna menentukan strategi intervensi yang optimal. Penelitian dilakukan dengan metode studi pustaka terhadap 281 artikel dari database PubMed, ScienceDirect, Garuda, dan Google Scholar, yang diseleksi dan dianalisis secara sistematis. Hasil analisis menunjukkan bahwa pemberian Acyclovirpaling efektif pada fase prodromal, dengan kombinasi kortikosteroid mampu mempercepat penyembuhan. Suplementasi vitamin B12 dan D berkontribusi dalam mendukung sistem imun, sedangkan penggunaan klorheksidin glukonat 0,2% efektif dalam mencegah infeksi sekunder. Faktor stres diidentifikasi sebagai predisposisi kekambuhan, sehingga edukasi manajemen stres berbasis konsep 4M (Menghindari, Mengubah, Mengadaptasi, Menerima) menjadi penting. Disimpulkan bahwa pengelolaan herpes labialis yang optimal memerlukan pendekatan farmakologis terpadu dan intervensi psikososial. Penelitian lanjutan diperlukan untuk pengembangan vaksin HSV-1 dan peningkatan program edukasi pencegahan berbasis masyarakat. Kata Kunci: Herpes Labialis, Antivirus, HSV